The Analysis Of Service Quality Increasing Outpatient Satisfaction At Al Islam Hospital Bandung - Mare A, Fauzan; Girsang, Ermi; Nasution, Sri Lestari Ramadhani (UNIVERSITAS PAKUAN, 2020)
The aim of the research was to determine the quality of service on outpatient satisfaction at Al Islam Hospital Bandung. where this research uses quantitative research methods. where this research was conducted in the Clinical Pathology Laboratory unit by distributing 45 questionnaires to 45 outpatient respondents. The results of the research show that the spearmen's rank correlation calculation is 0.92, indicating that the service quality variable has a very strong relationship with patient satisfaction. Calculation of the determinant coefficient obtained a result of 84.6%, indicating that the service quality variable has an influence on patient satisfaction of 84.6%. The conclusion obtained from the results of this research is that the quality of laboratory services has a very strong influence on outpatient satisfaction